Hubungan Penggunaan Media Sosial dan Self-Compassion dengan Harga Diri pada Mahasiswa Keperawatan Tingkat Akhir di Universitas Indonesia Maju Tahun 2024 - Audita Taza Suryanata; Indri Sarwili; Nining Rukiah (Pusat Riset dan Inovasi Nasional, 2025)
Social media has become an integral part of students' daily lives in the digital era. However, it also poses risks, such as negative social comparisons, which impact self-compassion and self-esteem. This study investigates the relationship between social media use, self-compassion, and self-esteem among final-year nursing students. Utilizing a cross-sectional correlational design, data were collected from 144 respondents at Universitas Indonesia Maju using validated questionnaires. The findings revealed a significant relationship between social media use and self-esteem (p=0.018) and between self-compassion and self-esteem (p=0.000). This study highlights the importance of fostering self-compassion and promoting healthy social media use among students to enhance their psychological well-being.